Effect of different milling methods on physicochemical and functional properties of mung bean flour - Yu, Shibo; Wu, Yanchun; Li, Zhenjiang; Wang, Changyuan; Zhang, Dongjie; Wang, Lidong (Frontiers in Nutrition, 2023)
There needs to be more information concerning the effect of different milling methods on the physicochemical properties of whole-grain mung bean flour. Therefore, the physicochemical properties of whole grain mung bean flour were analyzed using universal grinders (UGMB), ball mills (BMMB), and vibration mills (VMMB). The results showed that the particle size of the sample after ultrafine grinding treatment was significantly reduced to 21.34μm (BMMB) and 26,55μm (VMMB), and the specific surface area was increased. The particle distribution was uniform to a greater extent, and the color was white after treatment. Moreover, the water holding capacity (WHC), oil holding capacity (OHC), and swelling power (SP) increased, and the bulk density and solubility (S) decreased. The Rapid Viscosity Analyzer (RVA) indicated that the final viscosity of the sample after ultrafine grinding was high. Furthermore, rheological tests demonstrated that the consistency coefficient K, shear resistance, and viscosity were decreased. The results of functional experiments showed that the treated samples (BMMB and VMMB) increased their capacity for cation exchange by 0.59% and 8.28%, respectively, bile acid salt adsorption capacity increased from 25.56 mg/g to 27.27 mg/g and 26.38 mg/g, and nitrite adsorption capacity increased from 0.58 mg/g to 1.17 mg/g and 1.12 mg/g.